The man in the dog park: coming up close to homelessness - Small, Cathy (Cornell University Press, 2020)
"A decade ago, two dog owners met in a dog park, one an anthropologist, the other a homeless veteran with a felony record. The collaboration that came out of their emerging friendship led to this book and came to include a union researcher who had worked in a homeless shelter and surveyed day laborers. Together, the authors offer an ethnographic look at what it takes to be homeless, told through interviews and encounters with dozens of homeless people. Throughout the book, we are privy to exchanges that take place in the diverse contexts ranging from a shelter, a pawn shop, and a panhandling corner to a housing office, a plasma 'donation' center, and a car that serves as home"--